2003
DOI: 10.1096/fj.02-1191fje
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning with erythropoietin protects against subsequent ischemia‐reperfusion injury in rat kidney

Abstract: Improving the ability of the kidney to tolerate ischemic injury has important implications. We investigated the effect of recombinant human erythropoietin (rHuEPO) treatment on subsequent ischemia/reperfusion (I/R) injury and evaluated the role of heat shock protein (HSP) 70 in rHuEPO-induced renal protection. rHuEPO (3000 U/kg) was administered 24 h before I/R injury, and rats were killed at 24, 48, and 72 h after I/R injury. Pretreatment of rHuEPO resulted in the following: i) decreased serum creatinine leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
156
1
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(172 citation statements)
references
References 53 publications
11
156
1
4
Order By: Relevance
“…(C) Blinded scoring for acute tubular necrosis revealed better preservation of renal morphology after FG-4497 compared with Veh independent of the immunological constellation ( * , P Ͻ 0.05). confirmed that a number of genes previously identified as HIF-dependent are inducible in the kidney, including EPO, which has previously been demonstrated to be nephroprotective in renal ischemia-reperfusion models (30)(31)(32)(33), and HO-1, which has also been shown to improve short-and long-term graft function in the same rat model (34,35). In addition, HIF activation facilitates cellular anaerobic metabolism by inducing Glut-1 or enzymes involved in glycolysis.…”
Section: Discussionsupporting
confidence: 71%
“…(C) Blinded scoring for acute tubular necrosis revealed better preservation of renal morphology after FG-4497 compared with Veh independent of the immunological constellation ( * , P Ͻ 0.05). confirmed that a number of genes previously identified as HIF-dependent are inducible in the kidney, including EPO, which has previously been demonstrated to be nephroprotective in renal ischemia-reperfusion models (30)(31)(32)(33), and HO-1, which has also been shown to improve short-and long-term graft function in the same rat model (34,35). In addition, HIF activation facilitates cellular anaerobic metabolism by inducing Glut-1 or enzymes involved in glycolysis.…”
Section: Discussionsupporting
confidence: 71%
“…Similarly, its renoprotective effect in ischemia-reperfusion renal injury, as the most common cause of ARF in the community was also reported (15,31). It seems that erythropoietin is not solely a hormone charged with regulating the proliferation and differentiation of erythroid progenitor cells (33,34). Its erythropoietic function is mediated by antiapoptotic pathways, mainly involving Akt and the Bcl-2 gene family in bone marrow.…”
Section: Discussionmentioning
confidence: 90%
“…72 The kidney is protected by EPO in the setting of both ischemic and toxic injuries. [73][74][75] In ischemic injury with reperfusion, EPO prevents apoptosis of tubular epithelial cells as well as mediates intense mitotic activity of the surviving population of proximal tubular epithelial cells. 73 The skin has also been shown to be protected by EPO in rodent flap models.…”
Section: Epo Signaling In Nervous System Cellsmentioning
confidence: 99%